Удосконалення системи маркетингового управління для підвищення адаптаційних можливостей аграрних підприємств - Багорка, Марія Олександрівна; Bahorka, Mariia; Абрамович, Інна Ананіївна; Abramovych, Inna (Ужгородський національний університет, 2024)
В статті розкрито теоретичні особливості концепції маркетингового управління, дефініції даного поняття та основні проблеми з якими стикаються аграрні підприємства при реалізації даної концепції. Сформовані рекомендації у вигляді маркетингових рішень, щодо удосконалення системи маркетингового управління з метою підвищення адаптаційних можливостей аграрних підприємств в нестабільних та небезпечних умовах функціонування. Встановлено, що розширення асортименту продукції може допомогти зменшити ризики втрат у разі коливань попиту або цін на ринку. Адаптація виробництва до змінних умов та швидка реакція на ринкові зміни, застосування технологій та інновацій можуть забезпечити підприємству конкурентні переваги та зменшити вплив нестабільності ринку. Виокремлено підсистеми управління внутрішніми ресурсами та факторами зовнішнього середовища, які пов’язані між собою таким чином, що дозволяють залучити невикористані резерви маркетингового потенціалу підприємства в господарський обіг. The article reveals the theoretical features of the concept of marketing management, the definition of this concept, and the main problems faced by agricultural enterprises when implementing this concept. Recommendations in the form of marketing solutions have been formed, regarding the improvement of the marketing management system in order to increase the adaptation capabilities of agrarian enterprises in unstable and dangerous conditions of operation. The marketing concept of management is not just a component of the marketing system, but a separate philosophy of the functioning of enterprises. This concept is the main prerequisite for effective marketing activities at the current stage of development, as it is able to cover all marketing means and direct them to achieve marketing goals. Expanding the product range is an important solution to reduce the risk of losses in the event of f luctuations in market demand or prices. Growing different crops with different maturity dates or producing different types of crops will allow agribusinesses to distribute risks between different areas of production. The search for new sales markets will allow enterprises to reduce the risks of dependence on one market and expand their sales opportunities, but the implementation of risk management systems will allow enterprises to effectively analyze and assess risks and make strategic decisions for their management. The development of partnership relations will allow enterprises to combine resources and reduce risks, jointly responding to changes in the market. It has been found that some of the most influential issues, questions and challenges of marketing management can be closely related to various changes in today’s marketing environment – the changing importance of marketing communication channels and media, the growing influence of social media, the increased communication with customers and the influence of word of mouth, the need in marketing reporting, changes in marketing technologies and methods. Adaptation of production to changing conditions and quick response to market changes, application of technologies and innovations can provide the enterprise with competitive advantages and reduce the impact of market instability. Subsystems of management of internal resources and factors of the external environment are singled out, which are interconnected in such a way as to allow attracting unused reserves of the enterprise’s marketing potential into economic circulation.
Improvement of the marketing management system to increase the adaptability of agricultural enterprises
Keywords: маркетингове управління; marketing management; аграрні підприємства; agricultural enterprises; маркетингове середовище; marketing environment; фактори впливу; influencing factors; ринок; market; адаптація; adaptation; ресурси підприємства; enterprise resources